The Relation between Mean Platelets Volume and Obesity among patients in the Primary Health-care Centers at National Guard in Jeddah, Saudi Arabia - Alzahrani, Abduallah; Alshehri, Yasmeen; Alageel, Nourah; Bakraa, Roaa; Rawas, Renad; Alwagdani, Raghed (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Obesity is excess and fat accumulation that lead to negative effects on health. Many studies found an association between obesity and MPV. MPV is a determinant of platelet function, since platelet size has been proven to reflect platelet activity, which is an useful predictive biomarker for a variety of diseases. This is the second study in which MPV was evaluated in obese patients in KSA. AIM: The aim of study is to evaluate the relation between MPV and obese patients without metabolic risk factors at NGHA Jeddah, KSA. Secondary objectives are to compare between genders and to evaluate the association between total platelets count and obesity. METHODS: This was a cross-sectional study, A. Inclusion criteria: For the first group, any patient with BMI ≥ than 30 kg/m2 aged 18 years or more. Second group, non-obese aged 18 years or more. Exclusion criteria: Metabolic risk. RESULTS: There were 279 participated in this study. Most of the participants 214 (72.1%) were females, and 83 (27.9%) were males (Table 1). The mean age was 33.39 ± 10.19. There were 148 (49.8%) participants with normal BMI level, and 149 (50.2%) considered as obese. For MPV classification, 287 (96.6%) were normal, and 10 (3.4%) were high. In this case–control study, we found no significant evidence relating the association between MPV and obesity. CONCLUSION: In this study, we found no significant difference between MPV and platelet count between them. However, there was a significant positive week correlation between BMI and age with p = 0.0001.